Knowledge on diseases, practices, and threats of drugs residues in chicken food chains in selected districts of Dodoma region, Tanzania - A. Chota (Elsevier, 2021)
SUMMARY: Raising chickens is a rapidly growing subsector in the livestock industry. However, low biosecurity results in increased disease spread and the use of drugs in chicken flocks. Increased use of drugs threatens public health, as it poses risks of drug residues and resistant pathogens escaping into chicken food chains or infecting humans respectively. A cross sectional questionnaire survey and on-field clinical and postmortem diagnoses were carried out to establish farmers' awareness of diseases, drugs, and withdrawal times. It was established that 82% (n = 200) of local chicken keepers strongly agreed that, Newcastle disease was a major problem whereas, 43.5% (n = 200) of the farmers who kept layers strongly agreed that Fowl typhoid was the major problem. Concurrent occurrence of Ascaridia galli infestations and Coccidiosis had a significant association with local chickens (odds ratio [OR] = 7.2, 95% confidence interval [CI], 3.6–14.4, P < 0.05) whereas, concurrent infections of salmonellosis and colibacillosis had a significant association with mortality in layers (OR = 2.8, 95% CI, 1.6–5.2, P < 0.05). In local chickens, 91.1% (n = 200) relied on prophylactic drugs and in layers, 62.5% (n = 200) relied on treatment and vaccination for disease control, and only 48.2% (n = 200) and 24% (n = 200) respectively, knew about the withdrawal period. Oxytetracycline in 62 and 43.5%, enrofloxacin in 9 and 19.5%, and tylosin in 5 and 26.5% of local chickens and layer keepers respectively, were the most commonly used drugs. High mortality, mean 94.79 (SE; 86.05–103.53) per flock life span was observed in layers. Mortality resulting from diseases results in the continuous use of antibiotics in chicken flocks, as a result, with or without knowledge of drug withdrawal periods, the products and by-products sent into the food chain pose a significant public health concern.